Análise do discurso digital: entre a equivocidade da linguagem e a hipertrofia do imaginário nas redes sociais - Andrade, Bruno Fonseca de Oliveira (2020)
This research, based on Materialist Discourse Analysis (PÊCHEUX, 1997c; 2006), has the objective of producing a critical reflection about the relationship of the subject from the late capitalism builted over the neoliberal ideological formation (EVANGELISTA, 2007 e HAN, 2018b) with the digital tech (DIAS, 2018): about how this technology crosses the subject´s imaginary, his historical memory and his relation with the language. Our hypothesis is, as far, that the digital materiality of discourse puts the internet user in a contradiction between the misunderstanding over digital information (because of it´s excess, acceleration, fragmentation and very often lost context); and the hypertrophy of his imaginary (the strong and unreflected need of meaning for the impossible real of late capitalism on crisis). This contradiction, as we suppose, is multi-complex because works over idealizations and discourses even about language and digital tech itselves, both related with politics. To make happen the analysis, then, WHERE cut out (ORLANDI, 1984) 19 discoursive archives from digital materiality thru printing screenshots method. Those archives, by it´s turn, WHERE organized to a corpus meaning to contribute with the understanding over the digital reading gestures (PÊCHEUX, 1997b): a way of relating with the language that´s increasingly quantitative and less narrative (HAN, 2018a). As we try supporting here, therefore, is that new manner of being in language that seems to be one of the latent and structural causes of post-truth (DUNKER, 2017) and fake news success in brazilian network nowadays.